Biomolecule-based pickering food emulsions: Intrinsic components of food matrix, recent trends and prospects. (March 2021) - Niroula, Anuj; Gamot, Tanesh D.; Ooi, Chien Wei; Dhital, Sushil
Abstract: Dietary fat in food matrix plays an important role in improving the bioaccessibility of lipophilic micronutrients. Conventionally, surfactants and amphiphilic biopolymers have been used to stabilize the lipid and aqueous phase. Recently, the particle-stabilized emulsions, or referred to as 'Pickering emulsions', are studied extensively due to their better stability and potential applications in addition to the benefits of conventional emulsions. Inorganic particles are often criticized for causing irritation, damage to tissues and environment-related issues; hence biopolymers have emerged as promising Pickering particles. Hydrocolloids especially polysaccharides and proteins have been widely studied for their potential as a biopolymer-based Pickering particle and used in food-grade applications. However, particle properties like wettability, surface charge, size, and shape determine their applicability as Pickering particle. Majority of previous studies involved the model aqueous systems (water or buffer) as a continuous aqueous phase. In this review, the roles of intrinsic food-components like salts, pH, surfactants and colloids of food matrix and their potential in developing food-grade Pickering emulsions are discussed. Different strategies for the inclusion of lipophilic bioactive molecules in food-grade Pickering emulsions were systematically reviewed. Also, investigations on other aspects of developing food-grade Pickering emulsions, including sustainability of processing, particle modification strategies, and development of innovative Pickering food products, are on the rise. Further investigations in these areas could elaborate the scope of Pickering stabilization of food matrix and extend food-grade applications of biomolecule-based Pickering emulsion in nutraceuticals, pharmaceuticals and cosmeceuticals. Graphical abstract: Image 1 Highlights: Biopolymers with specific properties can act as Pickering particles. Salt, pH, surfactants and colloids are inevitable factors of food matrix. Food factors could make Pickering stabilization challenging. Particle compatibility with food factors governs emulsion traits. Bioactive molecules inclusion in Pickering emulsion can be tuned.